(untitled) (Global Journal of Computer Science and Technology, 2023)
Cryptocurrency is the innovation that has changed the way of life most significantly over the past ten years Bitcoins is a term that often comes up when discussing the blockchain system Although they are not identical Ethereum and Cryptocurrency nevertheless remain widely misunderstood Innovative technologies had to be created as a result from rising degrees of globalization These groundbreaking innovations improve the speed of international trade There are many technical experiments some of them were successful whereas others died or required development The decentralized ledger technology its benefits and methods for consensus are described on this article